2016
DOI: 10.4269/ajtmh.16-0056
|View full text |Cite
|
Sign up to set email alerts
|

P2X7R Gene Polymorphisms are Associated with Increased Risk of Pulmonary Tuberculosis in the Tibetan Chinese Population

Abstract: Abstract. In this study, we aim to explore the correlation between single nucleotide polymorphisms (SNPs) in the P2X7R gene and pulmonary tuberculosis (PTB) susceptibility in the Tibetan Chinese population in China. We examined 467 patients with active PTB and 504 healthy controls living in Xi'an and the surrounding area. Eight P2X7R SNPs were genotyped, and association analysis was performed. Odds ratios (ORs) and 95% confidence intervals (CIs) were tested by unconditional logistic regression analysis to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Identifying genetic vulnerabilities among populations can be very important for medical management (6, 35). For example, the identification of a P2X7R polymorphism has been associated with an increased risk of tuberculosis in mice (36) and later a Tibetan Chinese population (37). Further studies have suggested new therapeutic avenues through the use of natural agonists to P2X7R that promote death of Mycobacterium tuberculosis and apoptosis of infected monocytes and macrophages (38).…”
Section: A High Burden Of Disease Among Indigenous Populations In Thementioning
confidence: 99%
“…Identifying genetic vulnerabilities among populations can be very important for medical management (6, 35). For example, the identification of a P2X7R polymorphism has been associated with an increased risk of tuberculosis in mice (36) and later a Tibetan Chinese population (37). Further studies have suggested new therapeutic avenues through the use of natural agonists to P2X7R that promote death of Mycobacterium tuberculosis and apoptosis of infected monocytes and macrophages (38).…”
Section: A High Burden Of Disease Among Indigenous Populations In Thementioning
confidence: 99%
“…Through a comprehensive literature search and selection based on the inclusion criteria, 59 relevant case-control studies from 24 selected articles [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35] were included in the pooled analysis. There were 30 studies with 5247 cases and 7614 controls on rs3751143 (1513A > C), 19 studies with 3235 cases and 4685 controls on rs2393799 (−762 C > T), 3 studies with 2185 cases and 2107 controls on rs1718119 (Thr348Ala), 3 studies with 1994 cases and 2037 controls on rs208294 (His155Tyr), 2 studies with 2000 cases and 2006 controls on rs7958311, 2 studies with 1853 cases and 1797 controls on rs2230911 included into meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Several single nucleotide polymorphisms (SNPs) have been revealed that affect the function of this receptor which cause P2X7R loss-of-function (LOF) or gain-of-function (GOF) [8]. Many studies have inspected the association between P2X7 polymorphisms and risk of tuberculosis in various populations, but the findings were inconsistent [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. So we conducted an updated meta-analysis of all available eligible case-control studies published to date, focusing on the association between P2X7 polymorphisms and tuberculosis risk.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with tuberculosis, survival analysis suggested a weak association between rs7958311 polymorphism and treatment outcome, where each additional A allele of rs7958311 contributed to 59% increase in the probability of successful treatment outcome 18. In contrast, the A allele of rs7958311 was associated with an increased risk of pulmonary tuberculosis 19. Therefore, the role of rs7958311 variant in the functional mutation involving partial loss of P2 X 7 R pore function needs to be explored.…”
Section: Discussionmentioning
confidence: 99%